TEROBOSAN GAYA KAMPANYE POLITIK “TABRAK, PROF!” PADA PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024 - Amira Nurus Salma; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
The 2024 Presidential and Vice Presidential Elections marked a shift in political campaigning from a model based on large stages and one-way communication to campaigns that use social media and prioritize two-way interaction with the public. Amidst the dominance of public space by visual branding strategies and massive exposure of certain candidate pairs, a campaign program called “Tabrak, Prof!” was initiated by Mahfud MD, the vice presidential candidate paired with Ganjar Pranowo, which presented an open, participatory, and issue based dialogue format. The results of the study show that “Tabrak, Prof!” is a breakthrough in political campaign style that emphasizes a dialogical, informal, and participatory approach, with substantive messaging, especially related to legal and political issues, as well as distinctive visuals that build the candidate's image as a decisive and open figure. The campaign segmentation targets the younger generation, particularly Generation Z and millennials, who will be a significant voting bloc in the 2024 elections, by utilizing social media. This study concludes that “Tabrak, Prof!” represents a shift in the orientation of political campaigns towards a more dialogical, educational, and adaptive model in response to developments in digital media, while also serving as an alternative strategy in responding to competition in the 2024 elections.